Optimisation of layup type and fibre orientation in continuous-fibre reinforced components via anisotropy analysis. (1st May 2022) - Zimmerling, Clemens; Fengler, Benedikt; Krauß, Constantin; Kärger, Luise
Abstract: Continuous-fibre-reinforced plastics (CoFRP) have drawn increasing attention as load bearing structures in weight-sensitive applications. Typically, their full potential only unfolds after careful adjustment to load requirements. However, owing to the multitude of adjustable material parameters, determining a robust optimum is still a great challenge, especially when considering multiple load cases. In extension of existing approaches, this work proposes an optimality criterion (OC) based on principal stress analysis for simultaneous optimisation of layup type and fibre orientation in multi-load case scenarios. Three common layups are considered as layup types: quasi-isotropic (QI), bidirectional (BD) and unidirectional (UD) layups. Iterative application of the OC assigns each component region either QI-, BD- or UD-material at optimal orientation. The methodology is demonstrated using two generic geometries and one real-world structure. It is found to reliably allocate beneficial layup types at low computational effort and is thus deemed to facilitate a lean part design under consideration of multiple load cases.